The Relationship Of Knowledge Level And Attitude With The Treatment Of Primary Dysmenorrhea In Adolescents Princess In University Princess Dorms Indonesian Dharmas Year 2022 - Asri Widya Rizky; Ningsih Saputri; Sri Andar Puji Astuti (Journal of Midwifery and Nursing, 2023)
Dysmenorrhea is pain during menstruation that interferes with women's daily lives and encourages sufferers to do an examination or consult a doctor, puskesmas or come to a midwife. According to the World Health Organization (WHO) in 2017, the incidence of dysmenorrhea was 1,769,425 people (90%). The purpose of this study was to determine the relationship between the level of knowledge and attitudes with the treatment of primary dysmenorrhea in the female dormitory of Universiti Dharmas Indonesia in 2022. The research design used was an analytical survey research design with a cross sectional design using purposive sampling technique. This study was conducted from April to June and is located in the female dormitory of Dharmas Indonesia University. There are 64 respondents (72.7%) who have good knowledge, 56 respondents (63.6%) who have a positive attitude towards the treatment of dysmenorrhea and 82 respondents (93.2%) who treat primary dysmenorrhea non-pharmacologically. Meanwhile, according to the results of statistical tests, it is known that there is no relationship between knowledge and treatment of primary dysmenorrhea (p=0.800) and there is no relationship between attitude and treatment of primary dysmenorrhea (p=0.554). In conclusion, there is no significant relationship between knowledge and attitude with the treatment of primary dysmenorrhea